Abnormal Exercise Gas Exchange Before Pulmonary Emboli Diagnosis - Timothy Edwards, MS; Elisabet Børsheim, PhD; Andrew R. Tomlinson, MD (Mayo Clinic Proceedings: Innovations, Quality & Outcomes)
A 20-year-old male underwent diagnostic testing due to unexplained shortness of breath and chest discomfort. He had no previous medical problems and was not taking any medications. Initial evaluations included cardiopulmonary exercise testing (CPET), which yielded results that were reported as normal. However, over the following 2 months, his symptoms worsened considerably, including dyspnea with climbing stairs and then hemoptysis. Seeking urgent medical care, he presented to the emergency department, where he underwent further testing and was admitted to the hospital. Computed tomography angiogram reported bilateral pulmonary emboli. His parents requested a second opinion regarding the analysis of the CPET data, which revealed previously overlooked abnormalities. This overlooked data delayed pulmonary embolism diagnosis, and the patient ultimately required bilateral pulmonary thromboendarterectomy. In this case, we describe the hallmark signs of pulmonary vascular disease seen during CPET and offer clinical pearls to aid in timely detection.